Development of a Higher-Order Thinking Skills Assessment Instrument Using Socioscientific Issue Contexts on Chemical Solutions - Ervita Eka Rosawati (Yayasan Darussalam Bengkulu, 2026)
This study aimed to develop a HOTS assessment instrument using socioscientific issue contexts related to chemical solutions for Senior High School students. The HOTS assessment instrument was developed through five stages: preliminary study, item development, validation, trials, and implementation. The result of this development was a valid and reliable instrument consisting of 35 multiple-choice and 5 essay questions with 9 SSI contexts. The results were analyzed using the Partial Credit Model for Rasch modeling to examine the feasibility of the instrument. The validity and reliability of the assessment instrument were established by the item and person reliability, item and person separation, Alpha Cronbach value, item validity in the form of the infit value and the outfit MNSQ, Pt-measure correlation value, and unidimensionality. The developed assessment instrument provides a feasible tool for measuring students’ higher-order thinking skills in chemical solution topics using socioscientific issue contexts.